IT governance and information security guides, standards, and frameworks - Maleh, Yassine; Sahid, Abdelkebir; Alazab, Mamoun; Belaissaoui, Mustapha (Advances in cybersecurity management, 2022)
IT governance seems to be one of the best strategies to optimize IT assets in an economic context dominated by information, innovation, and the race for performance. The multiplication of internal and external data and increased digital management, collaboration, and sharing platforms expose organizations to ever-growing risks. Understanding the threats, assessing the risks, adapting the organization, selecting and implementing the appropriate controls, and implementing a management system are the activities required to establish proactive security governance that will provide management and customers the assurance of an effective mechanism to manage its risks. IT Governance and Information Security: Guides, Standards and Maturity Frameworks is a fendamental resource to discover IT Governance and Information Security. This book focuses on the guides, standards, and maturity frameworks for adopting an efficient IT Governance and Information Security Strategy in the organization. It describes numerous case studies from an international perspective and brings together industry standards and research from scientific databases. In this way, the book clearly illustrates the issues, problems, and trends related to the topic while promoting the international perspectives of readers. The book offers comprehensive coverage of the essential topics, including: IT governance guides and practices; IT Service Management as a key pillar for IT Governance; Cloud computing as a key pillar for Agile IT Governance; Information security governance and maturity frameworks. In this new book, The authors share their experience to help you navigate today's dangerous information security terrain and take proactive steps to measure your company IT Governance and information security maturity and prepare your organization to survive, thrive and keep your data safe. It aspires to provide a relevant reference for Executive Managers, CISOs, Cybersecurity professionals, Engineers, and Researchers interested in exploring and implementing efficient IT governance and information security strategies.